Lipid accumulation in the new oleaginous yeast Debaryomyces etchellsii correlates with ascosporogenesis. (September 2015) - Arous, Fatma; Triantaphyllidou, Irene-Eva; Mechichi, Tahar; Azabou, Samia; Nasri, Moncef; Aggelis, George
Abstract: The growth characteristics, lipid accumulation and composition during the life cycle of a newly isolated strain of Debaryomyces etchellsii were studied under nitrogen limiting conditions. This yeast, grown in batch flask or bioreactor cultures, reproduced asexually by buds when nitrogen was available in the growth medium, or sexually by ascospores after nitrogen exhaustion, producing more than 7 g L −1 biomass. During ascosporogenesis, an important increase in the cellular lipid content in dry cell mass occurred, i.e. from a mass fraction of 11.9% in the vegetative phase to 22.4%, in the ascosporogenic phase. During transition of D . etchellsii from batch to continuous cultures using dilution rates 0.026 and 0.019 h −1, a shift from sexual to asexual reproduction was observed. At 0.019 h −1, few pseudomycelia were also formed. The yeast synthesized lipids containing long chain fatty acids (mainly C16 and C18). Budded cells at steady-states contained only 8.6–9.3 % of lipids mass fraction per dry cell mass that were composed of oleic and linoleic acids and, to a lesser extent, of palmitic and palmitoleic acids. Neutral lipids were the major fraction represented 61.8–66.1%, of total lipids followed by phospholipids, which was the only fraction in which linoleic acid predominated over oleic acid. Graphical abstract: Highlights: Microbial oil production from oleaginous yeast Debaryomyces etchellsii was examined. Important increase in the cellular lipid content was observed during ascosporogenesis. D . etchellsii lipids are composed mainly of oleic acid followed by linoleic and palmitic acids. Fatty acid composition varies as function of the fermentation time and throughout the life cycle. Neutral lipids were the major fraction of total lipids followed by phospholipids.